Mean Platelet Volume as a Predictor of Atherosclerotic Severity in Non ST Elevation Acute Myocardial Infarction - Yuli Astuti; Budi Yuli Setianto; Nahar Taufiq (ACI (Acta Cardiologia Indonesiana), 2019)
Background: Acute myocardial infarction (AMI) is the leading cause of death in the world. AMI is classified into ST-elevation myocardial infarction (STEMI) and Non-ST elevation myocardial infarction (NSTEMI). Diagnosis and prediction of severity of atherosclerotic in NSTEMI is a challenge. Despite the risk stratification, 14-20% of patients that undergo coronary angiography have normal or non significant coronary artery disease. The role of platelet and the extent of atherotrombosis in patients with NSTEMI are interesting field of research. Mean platelet volume (MPV) reflects platelet size and reactivity. It can be used as a diagnostic marker and may have predictive value. This study aims to prove the role of MPV as a predictor of the degree of atherosclerotic based on Syntax score in patients with NSTEMI undergoing coronary angiography.Methods: This is a cross sectional study enrolled 86 subjects with NSTEMI. Blood samples were taken at the time of admission to the hospital. An MPV was measured by automated machine. Subsequent coronary angiography was performed using standardized method. Syntax score was determined to reflect the atherosclerotic severity. Statistical analysis was used to assess whether an MPV as a predictor of atherosclerotic severity based on Syntax score.Results: The chi-square analysis showed that high MPV could not be used as a predictor of the atherosclerotic severity based on Syntax score in NSTEMI patients (p value =0.5, prevalence ratio 1.15 (95% CI: 0.755-1.753). From multivariate analysis, only smoking factor had an independent relationship with Syntax score (p value =0.047; Odds ratio 2.531(95% CI: 1.012-6.328).Conclusions: High MPV cannot be used as a predictor of atherosclerotic severity based on Syntax score in NSTEMI patients.